Speed and Accuracy Comparison of Person Detection Using Pretrained CenterNet and Yolov3 - Friendly; Harizahayu; Sembiring, Zakaria (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Implementations of object detection by using common devices for general purpose application is not widely used for speed and prone to errors. Most of research in speed detection using known method such as Centernet, Yolov3, Fast-RNN has variant result since the computer used are different. This experiment try to conduct experiments for person detection with Centernet and Yolov3 method using commonly used computer only using CPU. Based on the experiments, Yolov3 can give a much better precision for person detection by 98.42% of mAP point while Centernet only 97%. In terms of processing speed, Centernet can give much better speed where it can detect a person in average 370ms better than Yolov3 with average of 1050 ms or 1 second.